1985
DOI: 10.1063/1.95948
|View full text |Cite
|
Sign up to set email alerts
|

Electron and hole impact ionization coefficients in GaAs-AlxGa1−xAs superlattices

Abstract: nating from the impurities commonly found in GaAs, i.e., C, 0, Si, S, can reasonably be ruled out by a careful comparison between the concentrations of these impurities and of EL2 and from their variations between the tail and the head of ingots. Weare then left to the conclusion that X = As;. This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…Kagawa, Iwamura, and Mikami 5 investigated the relationship between ionization coefficient ratios and the Al content x in a series of Al x Ga 1Ϫx As/GaAs MQWs with dimensions similar to those reported by Capasso et al 3 They concluded that xϭ0.45 gives significant enhancement in the ionization coefficient ratio with a reduction of excess multiplication noise corresponding to k(ϭ␤/␣)ϭ0.14 in McIntyre's noise model formula. 1 On the other hand, Juang et al 6 observed changes in the ␣/␤ ratio in Al x Ga 1Ϫx As/GaAs superlattices which were attributed to the suppression of the hole ionization coefficient, in contrast to the results reported by Capasso et al and Kagawa, Iwamura, and Mikami, which showed that the change in ␣/␤ ratio was due to the electron ionization enhancement. Franks 7 studied the dependence of the ionization coefficient on well and barrier widths using a series of Al 0.3 Ga 0.7 As/GaAs MQW structures with the period varying from 60 to 1000 Å and no appreciable change in the ␣/␤ ratio was observed in any of the structures.…”
Section: Introductionmentioning
confidence: 86%
“…Kagawa, Iwamura, and Mikami 5 investigated the relationship between ionization coefficient ratios and the Al content x in a series of Al x Ga 1Ϫx As/GaAs MQWs with dimensions similar to those reported by Capasso et al 3 They concluded that xϭ0.45 gives significant enhancement in the ionization coefficient ratio with a reduction of excess multiplication noise corresponding to k(ϭ␤/␣)ϭ0.14 in McIntyre's noise model formula. 1 On the other hand, Juang et al 6 observed changes in the ␣/␤ ratio in Al x Ga 1Ϫx As/GaAs superlattices which were attributed to the suppression of the hole ionization coefficient, in contrast to the results reported by Capasso et al and Kagawa, Iwamura, and Mikami, which showed that the change in ␣/␤ ratio was due to the electron ionization enhancement. Franks 7 studied the dependence of the ionization coefficient on well and barrier widths using a series of Al 0.3 Ga 0.7 As/GaAs MQW structures with the period varying from 60 to 1000 Å and no appreciable change in the ␣/␤ ratio was observed in any of the structures.…”
Section: Introductionmentioning
confidence: 86%
“…Although experiments were performed for simple multiquantum well devices using multiple materials systems, conflicting results have been reported using the GaAs/AlGaAs system. Though several experimental measurements of the ionization rates ratio in a GaAs/AlGaAs multiquantum well [63,[75][76][77] showed an enhancement of the electron to hole ionization rates, other experiments [78][79][80] failed to replicate these results. The nature of this discrepancy is still debated, which we discuss below.…”
Section: Simple Multiquantum Well and Staircase Apdsmentioning
confidence: 99%
“…10.31 the measured effective ionization coefficients for electrons (a^ and holes (o^) in the superlattice APD. 213 The solid lines in the figure are the least-squares fits given by a = 5.7xl0 6 exp(" L7xl° ) (10.47a) E -9 17vl0 6 a h = 5.5x10"exp( Z -WX1U ) ( Juang et al 214 have also systematically measured the electron and hole ionization coefficients in a series of Alo 4 Gao. 6 As/GaAs multiple quantum wells and superlattices with varying well and barrier thicknesses.…”
Section: Algaas/gaas Heterostructuresmentioning
confidence: 99%